Exploring the Impact of Leadership Styles on Followers’ Engagement in Corporations: A Cross-Generational and Cross-Cultural Perspective - NGAI ML, Malina (Digital Repository of Theses - SSBM Geneva, 2024)
Background As corporations strive to embrace diversity and effectively manage their multigenerational workforce, understanding the impact of leadership styles on employee engagement and job performance becomes crucial. This thesis examines the impact of leadership styles that positively influence employee engagement and job performance from the followers’ perspectives, with a focus on the preferences and experiences of different generations within corporations. The study also explores the potential mediation factors of generations and national culture in the relationship. Methods This study employs a large-scale questionnaire survey as the primary research method. Participating companies were selected based on the criteria that they have over 700 employees and an annual revenue exceeding Euro 80 million. This ensures a diverse sample that represents organizations of significant size, generations, and financial standing. The 531 sample consists of employees from 25 companies across 18 markets in Asia and Europe. Results The research findings provide compelling evidence regarding the significant influence of leadership styles on employee engagement. Specifically, supervisors who exhibit transformational and democratic leadership styles have a positive impact on employee engagement. On the other hand, employees working under laissez-faire leaders tend to report good performance but lower job satisfaction. The study identifies transformational and democratic leadership styles as the most desired leadership styles for enabling optimal employee performance. It is worth noting that a majority of respondents perceived their leaders as demonstrating a combination of two leadership styles rather than a single style. Furthermore, the study identifies "clear direction," "people-oriented behavior," and "recognition of achievements" as the top desired leadership behaviors among respondents. Interestingly, the study did not find significant differences in the effects of leadership styles on employee engagement and job performance across different generations. However, "being approachable" emerged as a desired behavior specifically for Generation Z respondents. Moreover, the research highlights the value placed by a high percentage of respondents on working in teams with diverse age groups. However, it is important to note that a smaller proportion of Generation Z respondents reported enjoying such diversity. Regarding the cultural context, no significant differences were detected in the effects of leadership styles on employee engagement and job performance between Asia and Europe. However, it is noteworthy that the democratic leadership style has a more positive influence on engagement in Europe, whereas in Asia, it has a more positive influence on job performance. Conclusion These findings highlight the importance of considering cultural differences and perceptions of performance when examining the impact of leadership styles. Further research is needed to explore the complex interplay between leadership styles, multigenerational diversity, and national culture in different organizational contexts. Understanding these dynamics can help organizations tailor their leadership approaches to maximize employee engagement and job performance across diverse cultural backgrounds.